2012
DOI: 10.3390/toxins4080605
|View full text |Cite
|
Sign up to set email alerts
|

Botulinum Neurotoxin A Injections Influence Stretching of the Gastrocnemius Muscle-Tendon Unit in an Animal Model

Abstract: Botulinum Neurotoxin A (BoNT-A) injections have been used for the treatment of muscle contractures and spasticity. This study assessed the influence of (BoNT-A) injections on passive biomechanical properties of the muscle-tendon unit. Mousegastrocnemius muscle (GC) was injected with BoNT-A (n = 18) or normal saline (n = 18) and passive, non-destructive, in vivo load relaxation experimentation was performed to examine how the muscle-tendon unit behaves after chemical denervation with BoNT-A. Injection of BoNT-A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…It should be noted that the clinical finding that BTX‐A causes decreased passive resistance to stretch is mainly ascribable to decreased hypertonicity of the spastic muscle, that is, reduced spasticity . Even in non‐spastic mouse muscle, large doses of BTX‐A were shown to cause reduced tone and disrupted stretch reflexes, leading to decreased passive resistance during stretching . Our experiments were also conducted on normal muscles, but the measurements did not include passive stretching with movement, as used in the evaluation of spasticity, and no reflex loop was operational.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It should be noted that the clinical finding that BTX‐A causes decreased passive resistance to stretch is mainly ascribable to decreased hypertonicity of the spastic muscle, that is, reduced spasticity . Even in non‐spastic mouse muscle, large doses of BTX‐A were shown to cause reduced tone and disrupted stretch reflexes, leading to decreased passive resistance during stretching . Our experiments were also conducted on normal muscles, but the measurements did not include passive stretching with movement, as used in the evaluation of spasticity, and no reflex loop was operational.…”
Section: Discussionmentioning
confidence: 99%
“…83 Even in non-spastic mouse muscle, large doses of BTX-A were shown to cause reduced tone and disrupted stretch reflexes, leading to decreased passive resistance during stretching. 84 Our experiments were also conducted on normal muscles, but the measurements did not include passive stretching with movement, as used in the evaluation of spasticity, and no reflex loop was operational. Therefore, modulation of muscle tone was not a part of our findings, and the increase in muscle passive force reflects enhanced muscular tissue stiffness.…”
Section: Discussionmentioning
confidence: 99%
“…The direct effect of intramuscular BoNT-A injection allows for the interruption of the hyperactive stretch reflex and modulation of passive muscle properties. Complementing this with kinesiotherapy may enable a better spread of the drug in the injected muscles and a consequently improved uptake of BoNT-A at the motor plates [29,30].…”
Section: Discussionmentioning
confidence: 99%
“…Haubruck et al have studied the passive biomechanical properties of the muscle-tendon unit in the healthy mouse gastrocnemius muscle during stretching, and have reported a decrease of stiffness by 25% after the botulinum toxin ( 17 ). Howren et al have reported a significant reduction of the muscle-tendon ratio after 6 weeks of botulinum toxin injection by monitoring the changes in length of the gastroc/soleus, as well as the Achilles tendon unit based on ultrasound images in 36 human clubfoot patients ( 18 ).…”
Section: Introductionmentioning
confidence: 99%